A Balance between Pro‐Inflammatory and Pro‐Reparative Macrophages is Observed in Regenerative D‐MAPS. Issue 11 (10th February 2023) - Liu, Yining; Suarez‐Arnedo, Alejandra; Shetty, Shamitha; Wu, Yaoying; Schneider, Michelle; Collier, Joel H.; Segura, Tatiana
Abstract: Microporous annealed particle scaffolds (MAPS) are a new class of granular materials generated through the interlinking of tunable microgels, which produce an interconnected network of void space. These microgel building blocks can be designed with different mechanical or bio‐active parameters to facilitate cell infiltration and modulate host response. Previously, changing the chirality of the microgel crosslinking peptides from L‐ to D‐amino acids led to significant tissue regeneration and functional recovery in D‐MAPS‐treated cutaneous wounds. In this study, the immunomodulatory effect of D‐MAPS in a subcutaneous implantation model is investigated. How macrophages are the key antigen‐presenting cells to uptake and present these biomaterials to the adaptive immune system is uncovered. A robust linker‐specific IgG2b/IgG1 response to D‐MAPS is detected as early as 14 days post‐implantation. The fine balance between pro‐regenerative and pro‐inflammatory macrophage phenotypes is observed in D‐MAPS as an indicator for regenerative scaffolds. The work offers valuable insights into the temporal cellular response to synthetic porous scaffolds and establishes a foundation for further optimization of immunomodulatory pro‐regenerative outcomes. Abstract : Implantation of microporous annealed particle scaffolds (MAPS) in the subcutaneous space leads to an increased angiogenic response when the crosslinker peptide is changed from L to D amino acids. This response is correlated with an increase in early cytokine expression, a balanced macrophage response including markers for reparative as well as inflammatory phenotypes, and a linker‐specific IgG2b immune response.